The Influence of Financial Literacy and Lifestyle on Student Financial Management Behavior - Putri, Afrizna Kurnia; Fatihudin, Didin; Maharani , Rieska (PT. Global World Scientific, 2024)
The purpose of this study was to determine the effect of financial literacy and lifestyle on Financial Management Behavior of Management Students of Muhammadiyah University of Surabaya. The following research uses a quantitative approach and analytical method multiple linear regression. The data collection technique in this study used a questionnaire with a sample of 181 respondents. The results of the following research show that financial literacy, and lifestyle simultaneously have a positive and significant effect on financial management behavior of management students of Muhammadiyah University of Surabaya. While partially the variable that greatly influences is financial literacy, the lifestyle variables have no significant effect on financial management behavior of management students of Muhammadiyah University of Surabaya. So with financial literacy a person can manage his finances appropriately and efficiently.